The Legal Protection against the Criminalization of Notary Positions and Land Deed Officials (PPAT) - Irfan, Irfan; Arifullah, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
It cannot be hidden, the position of the perpetrators of the position of notary public and land deed official (PPAT) is very vulnerable to becoming a â€œtarget for shootingâ€ by law enforcement officials. The term that is currently viral is